Functional Heterogeneity of Reelin in the Oral Squamous Cell Carcinoma Microenvironment - Zhang, Xinwen; Fu, Yong; Ding, Zhuang; Zhu, Nisha; Zhao, Mengxiang; Song, Yuxian; Huang, Xiaofeng; Chen, Sheng; Yang, Yan; Zhang, Caihong; Hu, Qingang; Ni, Yanhong; et al. (Frontiers in Oncology, 2021)
Background: Reelin, an extracellular glycoprotein, expressed on neuronal cells and participates into neuronal migration during brain development. Recently, Reelin also has a vital role in carcinogenesis. However, the role in oral squamous cell carcinoma (OSCC) has remained to be explored. The purpose of this study was to explore the roles of Reelin in OSCC. Methods: The expression of Reelin in cancer associated fibroblasts (ReelinCAF) and tumor cells (ReelinTC) was analyzed by Gene Expression Omnibus (GEO) database. Immunohistochemistry (IHC) was used to detect the spatial pattern of Reelin in 75 OSCC. The diagnostic and prognosis value of Reelin were evaluated and also verified by The Cancer Genome Atlas (TCGA) database. Primary CAFs from 13 OSCC patients were isolated to confirm Reelin expression. 39 OSCC peripheral blood were used to analyze the change of immunocytes based on Reelin levels by flow cytometry. The relationship between Reelin and tumor immune microenvironment in head and neck squamous cell carcinoma (HNSCC) tissues was performed by TISIDB and Tumor Immune Estimation Resource (TIMER) database. Results: Reelin was significantly upregulated in CAFs (ReelinCAF) in breast cancer, pancreatic cancer and rectal carcinoma, when compared with TCs (ReelinTC). The IHC results in OSCC also showed that Reelin levels were higher in CAFs. Upregulated ReelinTC was related to a decreased pN stage and distant metastasis. However, patients with enhanced ReelinCAF had a high risk of lymph node metastasis, poor worst pattern of invasion (WPOI) and distant metastasis, but showed comparable Ki-67 level in all OSCC patients, resulting in shorter overall survival (OS), disease-specific survival (DSS). Unexpectedly, Reelin in tumor-infiltered lymphocytes (ReelinTIL) correlated with postoperative relapse. Patients with high ReelinTIL, but not ReelinTC and ReelinCAF, had poor cytotoxicity of CD8+ T cells and higher radio of CD4/CD8 in peripheral blood. However, Reelin was positively associated with tissue-resident B cells and NK cells in tumor microenvironment. Conclusion: Reelin function versatilely in distinct cell types during the development of OSCC via governing tumor cell and stroma microenvironment.